Predicting the potential distribution of Corylus heterophylla in China under future climate change using an optimized MaxEnt model - Wang, Jingyu; Xing, Wang; Sun, Pengfei; Liu, Dali; Cheng, Chunxiang (Frontiers in Plant Science, 2025)
IntroductionCorylus heterophylla is native to East Asia, including northern and central China, southeastern Siberia, eastern Mongolia, Korea, Japan, and other adjacent regions, and its geographical distribution is highly sensitive to climate change. Investigating shifts in its suitable habitat under 1970-2000 and future climate conditions is crucial for the conservation and sustainable utilization of its germplasm resources.MethodsThis study employed an optimized MaxEnt model, integrating species occurrence records with multiple environmental variables, to simulate and analyze potential suitable habitats and their key environmental determinants under various climate scenarios.ResultsThe results demonstrated that the model configured with the feature combination (FC) of LQPH and a regularization multiplier (RM) of 3 achieved low complexity, minimal overfitting, and high predictive accuracy (AUC = 0.933). The dominant factors influencing the distribution were identified as Bio16 (Precipitation of wettest quarter, 39.5%), Bio9 (Mean temperature of driest quarter, 22.2%), Alt (Altitude, 16.2%), and Bio3 (Isothermality, 7.1%). The 1970-2000 climatically suitable area for C. heterophylla spans approximately 210.85 × 104 km2, accounting for 21.96% of China’s total land area. Projections under future climate scenarios indicate that the suitable habitat area for C. heterophylla will decrease slightly, primarily in low suitability zones, while high and medium suitability zones will expand. Its distribution pattern is expected to shift significantly northward while contracting southward, with the distribution centroid moving toward higher latitudes.DiscussionThese findings provide a scientific basis for conserving and sustainably utilizing C. heterophylla under climate change.